Long non‐coding RNA MEG3 promotes autophagy and apoptosis of nasopharyngeal carcinoma cells via PTEN up‐regulation by binding to microRNA‐21. Issue 1 (17th December 2020) - Lin, Liqiang; Liu, Xiaoli; Lv, Baotao
Abstract: Long non‐coding RNAs (lncRNAs) have been highlighted as attractive markers for diagnosis and prognosis as well as new therapeutic targets in multiple cancers, including nasopharyngeal carcinoma (NPC). Here, we attempted to investigate the underlying regulatory role of the lncRNA maternally expressed gene 3 (MEG3) in NPC development. As determined by RT‐qPCR, MEG3 expression was down‐regulated in NPC cells. Online RNA crosstalk analysis predicted the binding of miR‐21 to MEG3 and PTEN, respectively. MEG3 was validated to bind to miR‐21 while PTEN was identified as a target of miR‐21 by dual‐luciferase reporter gene assay. Exogenous transfection was done to change the levels of MEG3, miR‐21 and PTEN in HK‐1 cells to investigate their effects on the autophagy and apoptosis of NPC cells. The results suggested that MEG3 overexpression in HK‐1 cells up‐regulated PTEN and down‐regulated miR‐21, by which MEG3 further inhibited autophagy and apoptosis ability of NPC cells. The tumour formation ability was tested after injecting the HK‐1 cells into nude, mice and tumour growth was monitored. Consistently, MEG3 overexpression inhibited the tumour formation in vivo. Collectively, MEG3 promotes the autophagy and apoptosis of NPC cells via enhancing PTEN expression by binding to miR‐21.